Comparison the Effect of Ewe and Goat Colostrum Extracts on the Hematological and Biochemical Profiles: Rat as a Model - Afrah Sabeeh Mhyson (Journal of Global Pharma Technology, 2020)
This study was generated to provide information about the hematological and biochemical changes affected by exposing female rats to colostrum extracts of ewes and goats. As a start, 30 female rats were classified randomly into 3 groups (10 rats/each). The experiment was lasted for 30 days. Until the end of the experiment, a group received ewe colostrum extract (ECE) as 0.1ml orally/daily, another group was given goat colostrum extract (GCE) at 0.1ml orally/daily, the control group (C) was provided with normal saline at 0.1ml orally/daily. After the experiment was done, sacrificing of the tested animals was performed, and blood-based samples were obtained. These blood samples were tested for changes in the blood profiles using certain features such as RBCs counting, hemoglobin (Hb) level, packed cell volume (PCV), WBC counting, glucose (Glu) level, cholesterol (Ch) level, triglycerides (TAG), alkaline phosphatase (AP), alanine transferase (ALT), basophils (B%), eosinophils (E%), monocyte (M%), lymphocyte (L%), and neutrophils (N%). The results recognized significant (p<0.05) effects of the extracts on the RBCs, Hb, PCV, Glu, Ch, and TAG when compared with those in the C group. Furthermore, no significant (p>0.05) differences were provided from such effects on the WBCs, AP, and the ALT when compared with those in the C group. There were significant (p<0.05) effects of the extracts on the L% when compared with that in the C group. However, no significant (p>0.05) differences were provided from such effects on the B%, E%, M%, and N% when compared with those in the C group. No differences were noticed from these effects between both extracts on all those parameters. The study provides very important data about the effects of ewe and goat colostrum extracts on the hematological and biochemical characteristics in female rats that could be further used as supportive information for future studies.Keywords: Blood, Biochemical, Colostrum, Ewe, Goat, Parameters, Rat.